Impacto del crecimiento económico en la distribución del ingreso en el Ecuador, período: 2007-2014. - Quijosaca Pilamunga, Eduardo Manuel (2016)
This research is entitled “Impact of economic growth on income distribution in Ecuador 200-2014” and it evaluates the relationship between economic growth and income distribution and impact it gas on economic inequality and poverty relative to Kuznets Curve: Chapter I is concerned with the framework of the study and it includes the problem statement, formulation of the problem, overall goals and specific objectives, and the rational for research on economic growth and income distribution in Ecuador during the 2007-2014. Chapter II covers the theoretical framework of the study including the concepts, features, assumptions, equations, theories and models of economic growth, determinants of economic growth, calculations of GDP, features and theories explaining the distribution of income and causes and effects of income inequality and distribution policies by to government. Chapter III is concerned with the methodological framework of the study which used the deductive hypothetical method and collect data on economic growth and income distribution. Information is presented in data tables and figures and calculations were made using multiple linear regression. Chapter IV presents conclusions and recommendations on economic growth and income distribution in Ecuador, which could be useful for economic planning, and social policies in the country.